Efficacy and safety of acupuncture for postoperative gastroparesis syndrome: a systematic review and meta-analysis - Xv, Yichuan; Feng, Yiyi; Lin, Jiang (Frontiers in Medicine, 2025)
BackgroundPostoperative gastroparesis syndrome (PGS) is a common postoperative complication characterized by epigastralgia, nausea, and vomiting. Acupuncture is widely used to aid recovery, but its efficacy and safety have not been systematically evaluated.MethodWe retrieved randomized controlled trials (RCTs) using acupuncture as the primary intervention from six databases. After study selection and data extraction, a meta-analysis was performed using Review Manager 5.4.1. Study quality was assessed with the Cochrane risk of bias tool, and publication bias was quantitatively evaluated using Egger’s test and was corrected using the trimming and filling method.ResultsA total of 12 RCTs involving 709 participants (363 in the acupuncture group and 346 in the control group) were included. The meta-analysis showed a significantly higher overall response rate in the acupuncture group than the control group [RD = 0.16, 95% CI (0.11, 0.21), p < 0.001]. Acupuncture also reduced gastric tube indwelling time [MD = −2.36, 95% CI (−3.14, −1.59), p < 0.001], decreased gastric juice drainage [MD = −166.88, 95% CI (−176.57, −156.18), p < 0.001], and improved serum motilin levels [MD = 41.65, 95% CI (30.14, 53.15), p < 0.001]. Four studies reported no adverse events in either group, but the majority of studies did not provide safety data.ConclusionAcupuncture may alleviate clinical symptoms and shorten hospitalization, potentially by enhancing gastrointestinal motility. However, the lack of safety data in the majority of studies raises concerns about the reliability of these findings and the transferability of the results. Future trials should focus on rigorous randomization, blinding, and comprehensive safety reporting to improve the quality of evidence in this field.Systematic review registrationID: INPLASY202320035 URL: https://inplasy.com/inplasy-2023-2-0035/